Targeted Delivery of Lipid Nanoparticles by Means of Surface Chemical Modification - Gaspar, Diana P.; Faria, Vasco; Quintas, Joao P.; Almeida, Antonio J. (Current Organic Chemistry, 2017)
Background: Reaching the target cell has been the ultimate goal of nanoparticle-based drug delivery because many drugs do not have the adequate physicochemical properties to reach or be taken up by target cells. Therefore, site-specific drug delivery systems have been sought, aiming at overcoming many biological barriers, thus improving drug performance. Objective: Lipid nanoparticles emerged as a promising alternative for the usual colloidal drug carriers, prepared with non-toxic solid physiological lipids and stabilized by common pharmaceutical surfactants. In addition to the controlled or triggered release, solid lipid nanoparticles (SLN) can be designed to afford longer circulation times improving the efficiency of drug delivery to the site of action. Over the past 20 years, several passive or active functionalization approaches have been successfully applied to lipid nanoparticles intended for targeting. A variety of ligands may be functionally SLN-attached including various internalizable ligands, specific targeted peptides, saccharide ligands, or therapeutic molecules (e.g. antibodies or enzymes). Conclusion: The present review focuses on the surface modification of lipid nanoparticles either SLN, nanostructured lipid carriers (NLC), lipid drug conjugate nanoparticles (LDC) or lipid nanocapsules (LNC) with specific molecules with the aim of improving its therapeutic and targeting performance.
Keywords: Lipid nanoparticles